Study of prevalence rate of Giardia in children undergoing upper intestinal endoscopy in Tishreen University Hospital in Lattakia - سمرة, سوزان; إبراهيم, علي; مريشة, ريم (Latakia University Journal -Medical Sciences Series, 2022)
The study was performed at Tishreen University Hospital in Lattakia between December 2017 and June 2019. The purpose of the study was to determine the local prevalence of Giardia in children undergoing upper gastrointestinal endoscopy and evaluating the effectiveness of the duodenal aspirate test in diagnosing giardiasis and comparing it with stool test. The study included 125 children aged 1-16 years. We collected aspirate samples from 125 patients, and only 40 patients administered a stool sample. The result of the study showed that the prevalence of Giardia according to the aspirate test was 15.2%, while when comparing the results of the aspirate test with the stool test, the prevalence rates were 30% and 25%, respectively. The higher rate of infection was among children aged 4-7 years, followed by children aged 1-4 years. The most common clinical symptoms were abdominal pain (47.36%) and weight loss (42.10%). The infection rate of males (57.89%) was higher than that of females (42.10%).